Grief reaction and psychosocial impacts of child death and stillbirth on bereaved North Indian parents: A qualitative study. - Manoja Kumar Das (PLoS ONE, 2021)
Background Grief following stillbirth and child death are one of the most traumatic experience for parents with psychosomatic, social and economic impacts. The grief profile, severity and its impacts in Indian context are not well documented. This study documented the grief and coping experiences of the Indian parents following stillbirth and child death. Methods This exploratory qualitative study in Delhi (India) included in-depth interviews with parents (50 mothers and 49 fathers), who had stillbirth or child death, their family members (n = 41) and community representatives (n = 12). Eight focus group discussions were done with community members (n = 72). Inductive data analysis included thematic content analysis. Perinatal Grief Scale was used to document the mother's grief severity after 6-9 months of loss. Results The four themes emerged were grief anticipation and expression, impact of the bereavement, coping mechanism, and sociocultural norms and practices. The parents suffered from disbelief, severe pain and helplessness. Mothers expressed severe grief openly and some fainted. Fathers also had severe grief, but didn't express openly. Some parents shared self-guilt and blamed the hospital/healthcare providers, themselves or family. Majority had no/positive change in couple relationship, but few faced marital disharmony. Majority experienced sleep, eating and psychological disturbances for several weeks. Mothers coped through engaging in household work, caring other child(ren) and spiritual activities. Fathers coped through avoiding discussion and work and professional engagement. Fathers resumed work after 5-20 days and mothers took 2-6 weeks to resume household chores. Unanticipated loss, limited family support and financial strain affected the severity and duration of grief. 57.5% of all mothers and 80% mothers with stillbirth had severe grief after 6-9 months. Conclusions Stillbirth and child death have lasting psychosomatic, social and economic impacts on parents, which are usually ignored. Sociocultural and religion appropriate bereavement support for the parents are needed to reduce the impacts.